El análisis e interpretación financiera a los indicadores de rentabilidad para optimizar el control de la gestión empresarial - Guamán Campos, Tania Jacqueline (2015)
This research consists in the "THE ANALYSIS AND INTERPRETATION TO THE FINANCIAL INDICATORS OF PROFITABILITY TO OPTIMIZE THE CONTROL OF BUSINESS MANAGEMENT" to facilitate management decision-making in the company Leomari S. A. for the purpose of supporting the activities of the area by providing financial techniques that allow you to analyze and interpret the components of the Statement of Financial Position and the State Comprehensive results. It was determined that the management is unaware of the application of indicators, the decisions are taken based on the experience of the manager and financial data provided by the accounting area, which is certainly not giving positive results in the profitability of the company, which means that the financial analysis by the method indicators of liquidity, and profitability management will contribute to greater efficiency in the opportune decision making on the part of the administrator. Chapter 1 is formed by the bases and theoretical conceptions that contribute to the understanding of the problem to investigate and provides guidelines to give solution to the same. This research is qualitative approach and used a field research and documentary-literature, with a descriptive exploratory level to suit the needs and requirements of the problems found in the company Leomari S.A. in chapter 2 we will have the integrative proposal that will provide a solution to the problem raised in chapter 1 by setting objectives, phases of deployment and logistical resources that will be used in the implementation of the proposal. In chapter 3 will be an analysis of the technical dimension, social, economic and environmental of the implementation of the proposal, and finally, we present the conclusions and recommendations which are reached after apply the financial indices.